Aprender a ensinar frações a partir do conceito de atividade orientadora de ensino : um estudo com professores de quartos e quintos anos do ensino fundamental - Zeferino, Lidiane Chaves [UNIFESP] (2016)
The present work aims to adress the contribuitions to the teaching of fractions starting from a historical and cultural point of view, taken generally starting from the productions of Vigotsk, Davidov and the theory of activities propose by Leontiev (1983). Specially, in the organization of the teachings of concepts of fraction, the research shows as central issue investigate " How the organization of mathematics teaching, more specifically the concepts of fractions, starting from the contribuitions of the historical and cultural theory and the guiding activity of teaching, influences and its influenced by the development of theorical thinking of the teacher who teachs math in the fourth and fifth grade in the elementary school" For the substantiation of this research, we utilize as methodological references the historical dialectical materialism and as guiding principle the investigation of the teaching experiment, understood as a method of investigation who allows the study of the essence of internal relations between the different procedures of the education and teaching, which occured in the form of a extension course turned to continuing education of teachers of the 4th and 5th grade of elementary school. The collected data during the procces of investigation were analyzed and organized isolated: "The movement the movement of theoretical thought and the organization of fraction teaching". According with the results, the research shows that both the knowledge about the concept of fractions, as to the organization of teaching are anchored in the characteristics of empirical thinking, limiting the concept of fraction to its dimension of discrete quantification. Such context difficult the teaching and the learning of this concepts, because it does not set the relation with the essentials elements of the concept, for example the genesis of the fraction, therefore distancing from the development of the theoretical thinking.